DETEKSI POTATO VIRUS Y DENGAN ELISA PADA BENIH KENTANG (Solanum tuberosum L.) VARIETAS GRANOLA DAN ATLANTIK HASIL PENANGKAR BENIH KABUPATEN BANJARNEGARA - Jekki Irawan; Suparso Suparso; Budi Prakoso (Universitas Teuku Umar, 2018)
The aims of the research were finding the differencesin the production of tuber potatoes and detecting Potato Virus Y on various tuber generation from Banjarnegara Regency using Enzyme Linked Immunosorbent Assay (ELISA) test. This research was conducted in two stages. The first stage wasa survey and an interview on potato breeders in Banjarnegara district of Central Java province. The second stageis ELISA test in the Laboratory of Plant Breeding and Biotechnology, Agricultural Faculty, the University of Jenderal Soedirman, North Purwokerto, Purwokerto, Central Java. ELISAkit was obtained from Agdia. Inc Elkhar tIndiana, United States. Tubers of potatoes,Granola variety and Atlantic variety were obtained from potato breeders in Banjarnegara Regency. Survey and interview were conducted at seven seed breeders by asking questions about the process for producing potato tubers. ELISA test was performed on 1 g tuber/sample. Antigen wasextracted from the sample using 10 ml General Extract Buffer/sample. Then 100 ml solution of antigen was transfered into ELISA wells and incubated for 2 hours. After incubation the antigen solution was removed from the wells. Then the wells were washed using Phosphate Buffer Saline Tween (PBST) seven times. 100 ml enzyme conjugate was added/well and incubated for 2 hours. Enzyme conjugate solution was removed and washed using PBST eight times. Substratep-Nitrophenyl was added as much as 100 ml/well and incubated for 60 minutes. The result was read using a micro plate reader at 405 nm wave length.The results showed that, the way potato cultivation in order to produced seed varieties Granola and Atlantic using a screen house and aeroponics method were of effective way for produced free Potato Virus Y tubers. Results of tests using ELISA against Granola varieties and Atlantic of seed potatoes from six breeders in Banjarnegara Regency showed that, seed potato varieties Granola G4 from breeder Trubus contained of Potato Virus Y.Keyword: Tuber potatoes, Potato Virus Y, ELISA